mNutrition Tanzania Baseline Study - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
mNutrition was a five-year global initiative supported by the Foreign, Commonwealth & Development Office (FCDO) between 2013 and 2018, organized by GSM Association (GSMA), implemented by in-country mobile network operators, and evaluated by researchers from GAMOS, the Institute of Development Studies (IDS) and the International Food Policy Research Institute (IFPRI), with the objective of building effective mobile phone-based advisory services for improving nutrition outcomes. In Tanzania, mNutrition was implemented through the ‘Healthy Pregnancy, Healthy Baby’ (HPHB) SMS program and the service offered free customized health and nutrition information through pregnant women, mothers with newborns, and male supporters to promote good health-seeking behavior and improve knowledge and practices around optimal childcare and nutrition. To determine the causal effect of the program on nutritional outcomes, a cluster randomized control design was employed to randomly assign recipients to receive the messages. Household interviews were conducted before and after the intervention. Data collection was carried out in the three rural districts of the Iringa region: Iringa rural, Kilolo, and Mufindi. At baseline, 2833 households from 180 communities (90 treatment and 90 control) were interviewed. Interviews were conducted with both primary male and female members of the household. Among interviewees were 948 pregnant women and 1885 mother of a child under 12 months of age.